HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN MEROKOK PADA REMAJA DESA MARIRI LAMA KABUPATEN BOLAANG MONGONDOW TAHUN 2023 - Delia Kristia Manorek; Theo W. E. Mautang; Lucyana L. Pongoh (Yayasan Syalom Cipta Sumikolah, 2024)
Adolescence is a stage in human life where one begins to explore their abilities and develop social skills and self-identity. The development of emotions, psyche, and physical aspects during adolescence will occur rapidly, making it difficult for teenagers to find their identity, thus they cannot distinguish between what is good and what is bad. Adolescence is a group that is more vulnerable to addiction because this period is characterized by a high curiosity about various things that, without realizing it, may lead to problems. Smoking is one of the phenomena that is often encountered in everyday life, both in public places and educational settings. Smoking is one of the public health issues in Indonesia, considering that smoking is a risk factor for several chronic diseases that can lead to death. It seems like you didn't provide any text to translate. Please provide the text you'd like me to translate, and I'll be happy to help! Smoking behavior is not only practiced by men but also occurs during adolescence. The percentage of smoking among male residents aged ≤ 18 years in 2020 was 7.26%, in 2021 it was 7.14%, and in 2022 it was 6.54%. The percentage of smoking among residents aged ≥ 15 years shows that there are still adolescent residents and residents who consume cigarettes daily, which is greater than the residents who do not consume cigarettes daily. The trend of increasing numbers of teenage smokers and the younger age at which they start smoking is a particular concern due to the long-term health impacts.